Seawater Acidification Exacerbates the Negative Effects of UVR on the Growth of the Bloom-Forming Diatom Skeletonema costatum - Li, Futian; Li, Hangxiao; Xu, Tianpeng; Li, Shihu; Xu, Juntian (Frontiers in Marine Science, 2022)
Climate changes such as seawater acidification caused by rising atmospheric CO2 and increased UVR intensity resulted from shoaling of the upper mixed layer may interact to influence physiological performance of marine primary producers. But few studies have investigated long-term (>30 days) effects of UVR under seawater acidification condition, along with less attention on the differential effects of long- and short- wavelength UVA. In the present study, four spectral treatments (>280, >320, >360, and >400 nm) under two pCO2 levels (400 and 1000 μatm) were set to investigate the interactive effects of seawater acidification and UVR on the bloom-forming diatom Skeletonema costatum. The results showed that UVR decreased growth and effective quantum yield of PSII by 9-16% and 11-24% respectively, but it enhanced cell sizes significantly. Long- and short-wavelength UVA showed differential effects on cell volume and the effective quantum yield of PSII, especially at elevated CO2 level. Generally, seawater acidification depressed the growth, effective quantum yield of PSII, and cell volume by 6-18% and 8-39% of the tested speciesrespectively. Additionally, the contents of key PSII proteins (D1 and D2) decreased at elevated CO2. Elevated CO2 significantly increased the inhibition of UVR on growth in the >280 nm spectral treatment when compared with ambient CO2, while it alleviated the inhibition in the >360 nm spectral treatmentshowed no effects in other spectral treatments when compared with ambient CO2. Overall, the results indicate that effects of seawater acidification on the ubiquitous diatom are light wavelength-dependent.